A hospitalidade e o controle na fronteira entre o Brasil, o Paraguai e a Argentina sob a perspectiva do turista brasileiro - Welter, Viviane da Slva (2018)
This study aimed at reflecting on hospitality and control in the Triple Frontier, located between Brazil, Paraguay and Argentina. For this, it was based on bibliographical material on tourism, hospitality, border, territory and territorialities, control and power relations, besides a brief history and territorialities of the Triple Frontier. In order to expand the discussion this study also used field research with data collection and quantitative descriptive analysis to understand and present the qualification of the hospitality and control in the Triple Frontier under the perspective of the Brazilian tourist, who in stay in this border territory is well received due to all the facilities of infrastructure and reception, but also on the other hand, paradoxically, it is inserted in an environment of control when it decides to cross the border to go to Paraguay or Argentina. In addition to presenting the perceptions of the Brazilian tourist about the paradox of hospitality and control, this study discusses if hospitality and control are decisive factors for the return of the Brazilian tourist to Foz do Iguaçu and if this binomial contributes to develop or slow the tourism in the Triple Frontier.